A public awareness campaign for the Hope of the Nations Philippines, Inc. to propective donors of Davao City through brochures - Rosos, Ketka G.
This production thesis aimed to attract new potential donors and sponsors for Hope for the Nations ? Philippines, Inc (HFTN) through brochure. Attracting corporations to donate and sponsor to no-profit advocacies has become a competition. Hence, with other non-profit organization also seeking support from private sectors coming up with a more personal tool to communicate to the donors and sponsors in Davao City should be given attention. The key messages appropriate photographs and elements of design must be in accordance with each other to come up with an aesthetically appealing brochure. Photographs must tell a story and emotion to target the audiences? empathy as well as work together with the key message that will make the target audience donate and sponsor. Small non-profit organizations like HFTN Davao should develop a communication materials and strategies that effectively educate, involve and motivate donors to give and support their advocacies. A brochure can make a strong impact both visually and emotionally through a well-designed layout, to its strong, physical copy containing high-quality photos. The brochures can be distributed through many channels such as being sent through mail, given out at events, or delivered in personal calls that creates a more personal and direct approach than the electronic media.
Thesis (B.A. Communication Arts) -- University of the Philippines Mindanao
Keywords: Communication Arts -- Media Arts